Determinants of Grant Absorption in Indonesia: Evidence from Fiscal Capacity, Grant Management Experience, and Regional Heterogeneity - Farisa Noviyanti (Department of Public Administration, 2026)
This study examines how local fiscal capacity and previous grant management experience influence grant absorption performance in Indonesia. Grants are a crucial component of development funding with specific purposes and are executed through formal agreements. Because grants often require pre-financing, local fiscal capacity becomes an important determinant when proposing recipients, as stipulated in existing regulations. Using panel data from 546 regional governments for 2019–2023, this study applies fixed-effects and random-effects regressions with clustered standard errors. The analysis first tests aggregate grant absorption and then examines differences by funding source: foreign loans (FL), foreign grants (FG), and domestic revenues (DR). Results show heterogeneous effects: fiscal capacity negatively affects FL absorption but positively affects FG, while neither overall grants nor DR grants are significantly influenced. Prior grant management experience improves FL absorption but has no significant effect on FG or DR. The interaction between fiscal capacity and experience is marginally positive for FL but strongly negative for FG, indicating distinct moderation patterns across funding types. Audit quality shows no direct relationship with absorption, while geographic disparities persist, with Java outperforming eastern regions. These findings highlight the need for tailored grant absorption strategies that consider both funding characteristics and regional capacity gaps.